2022
DOI: 10.1039/d2cp02654f
|View full text |Cite
|
Sign up to set email alerts
|

In-depth theoretical understanding of the chemical interaction of aromatic compounds with a gold nanoparticle

Abstract: Gold Nanoparticles (GNPs), owing to their unique properties and versatile preparation strategy, have been demonstrated to exhibit promising applications in diverse fields, which includes bio-sensors, catalysts, nanomedicines, radiotherapy. Yet, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Now that the geometry is optimized, and vibrational modes and Raman spectra have been calculated. Using GGA DFT calculations, Tandiana et al 50 have recently demonstrated that the IR spectrum of aromatic compounds in interaction with a gold nanoparticle was changed as a result of the molecular orientation: they have considered the ''flat'' and ''perpendicular'' configurations. Here, we have calculated the Raman spectra of the different orientations shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Now that the geometry is optimized, and vibrational modes and Raman spectra have been calculated. Using GGA DFT calculations, Tandiana et al 50 have recently demonstrated that the IR spectrum of aromatic compounds in interaction with a gold nanoparticle was changed as a result of the molecular orientation: they have considered the ''flat'' and ''perpendicular'' configurations. Here, we have calculated the Raman spectra of the different orientations shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The above stretching frequency range can be assigned to the different mode of C=O binding with Au 0 and Au + surface. [17] In addition to MetÀ S!Au + interaction, confirmed by XPS, the formation of Au + is also stabilized by the carboxylate group. The competing binding modes of Met(S) and Met(CO À…”
Section: Effect Of Met Concentrationmentioning
confidence: 94%
“…32 Recently, a theoretical study by Tandiana et al reported the chemical interactions of aromatic compounds with AuNPs and predicted noncovalent interactions with dative, dispersive, and repulsive nature. 33 The interactions of NPs with neurotransmitters, which are necessary for brain cell communication, are one of the attractive areas of research. The development of novel treatment strategies for neurological disorders can be improved by an understanding of how NPs interact with neurotransmitters.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a theoretical study by Tandiana et al. reported the chemical interactions of aromatic compounds with AuNPs and predicted noncovalent interactions with dative, dispersive, and repulsive nature …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation